Sustainable Design with Circular Thinking: Reinventing Teak Wood Waste into Decorative Products (Architecture Image Studies, 2025)
As a major global timber producer, Indonesia struggles more with furniture industry wood waste as well as a growing timber scarcity. This paper looks at the sustainable use of teak wood waste—a high-quality by-product typically discarded during furniture production—as a substitute material for decorative objects, including minimalist lamps. The project aims to explore how circular design ideas might be applied to transform industrial by-products into value-added products while promoting environmental responsibility and aesthetic creativity. By means of qualitative techniques combining literature analysis, market observation, and stakeholder participation, the study identifies viable methods to recycle teak wood waste. Material selection is given great importance depending on wood thickness and grain quality to ensure fit for certain design applications. A SWOT study examines the strengths, weaknesses, opportunities, and threats of teak wood waste use in the creative sector. Results show that although minimalist design ideas raise material use and lower secondary waste, they also preserve the natural appeal of teak wood. Market trends show growing customer demand for sustainable, artistically unique products, which strongly supports circular product manufacture. Still to be addressed, however, uneven material quality and technological limitations. This article contributes to the discussion on sustainable design by providing a consistent framework for converting waste materials into high-value manufacture. It also offers strategic concepts for lawmakers, manufacturers, and designers attempting to balance environmental goals with market-oriented product development.